A Heuristic Model for Designing Interventions in Multicultural Mental Health Encounters: The Case of a Community Mental Health Center among the Mapuche of Chile. (20th July 2021) - Wiencke, Markus
Abstract: In this paper, I develop the integrative concept of "shared experience of sense" as a heuristic model to design interventions in multicultural health encounters in the field of mental health promotion. For this purpose, I use extensive ethnographic material from the Mapuche's territory in Chile, analyzing the interactions between an outpatient community mental health center and deinstitutionalized patients in their home settings. The patients and their families navigate the medical pluralism of their domestic settings and make varying use of each of the different therapeutic options that are available to them, offered by the outpatient community mental health center, Indigenous healers, and Pentecostalism. The concept of "shared experience of sense" characterizes a specific form of meaning‐making that may be beneficial to health in mental illness. This "positive" meaning making is made possible by a person's emotional and physical participation in the social events of therapeutic settings. In this regard, I highlight the bridges that the community mental health center builds to the everyday lives of patients and their families. Because of the support and access to resources provided by such therapeutic settings, persons are able to cope with their illness in everyday life, which can mean different things depending on the context. This is what I mean when I refer to "health promotion" in this article.